Pengaruh Empat Galur Bakteri Pemacu Pertumbuhan Tanaman dan Waktu Inokulasi Virus terhadap Keparahan Penyakit Daun Keriting Kuning Cabai - Hari Priwiratama; Sri Hendrastuti Hidayat; Widodo . (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Plant growth-promoting rhizobacteria (PGPR) has effectively reduced infection of pathogens. Bacillus polimixa BG25, B. subtilis SB3, Pseudomonas fluorescens PG01, P. fluorescens S32, and their combinations were used as seed treatment. Bemisia tabaci (Hemiptera: Aleyrodidae) was used to inoculate Geminivirus at 3, 5, and 6 weeks after planting. Seeds without any bacteria treatment were used as controlled plant. Treatment of PGPR and time of inoculation were significantly effect disease intensity, but not incubation period. Late infection of Geminivirus reduced disease intensity. Based on measurement of plant height, number of branch, and flowers it was concluded that some bacterial treatments was significantly effect plant growth. Key words: Bemisia tabaci, Geminivirus, PGPR, plant growth promoting rhizobacteria